Use of Rice Husk Ash as Cementitious Material in Concrete - Bheel, N.; Abro, A. W.; Shar, I. A.; Dayo, A .A.; Shaikh, S.; Shaikh, Z. H. (Engineering, Technology & Applied Science Research, 2019)
In this research, rice husk ash (RHA) was used as a partial substitute for cement in concrete to reduce its cost, and alternative processing methods using agricultural/industrial waste were found. The main objective of this study was to determine the fresh (flowability) and hardened (splitting tensile strength and compressive strength) concrete properties using RHA at 0%, 5%, 10%, 15% and 20% by weight. A total of 90 concrete samples (45 cubes and 45 cylinders) were prepared and cured on 7, 14, and 28 days to the design of target strength 28N/mm2, and ultimately, these concrete specimens were tested on UTM. Three concrete specimens were cast for each proportion and ultimately the average of the three concrete samples was taken as the final result. The flowability of fresh concrete decreases with increasing content of RHA in concrete. The results showed that the compressive and tensile strength of the concrete specimens increased by 11.8% and 7.31%, respectively by using 10% RHA at 28 days curing.